Emerging functions and clinical applications of exosomal microRNAs in diseases - Soudeh Ghafouri-Fard; Hamed Shoorei; Peixin Dong; Yadollah Poornajaf; Bashdar Mahmud Hussen; Mohammad Taheri; Nader Akbari Dilmaghani (Non-coding RNA Research, 2023)
Exosomes are an important group of extracellular vesicles that transfer several kinds of biomolecules and facilitate cell-cell communication. The content of exosomes, particularly the amounts of microRNA (miRNAs) inside these vesicles, demonstrates a disease-specific pattern reflecting pathogenic processes and may be employed as a diagnostic and prognostic marker. miRNAs may enter recipient cells through exosomes and generate a RISC complex that can cause degradation of the target mRNAs or block translation of their corresponding proteins. Therefore, exosome-derived miRNAs constitute an important mechanism of gene regulation in recipient cells. The miRNA content of exosomes can be used as an important tool in the detection of diverse disorders, particularly cancers. This research field has an important situation in cancer diagnosis. In addition, exosomal microRNAs offer a great deal of promise in the treatment of human disorders. However, there are still certain challenges to be resolved. The most important challenges are as follow: the detection of exosomal miRNAs should be standardized, exosomal miRNAs-associated studies should be conducted in large number of clinical samples, and experiment settings and detection criteria should be consistent across different labs. The goal of this article is to present an overview of the effects of exosome-derived microRNAs on a variety of diseases, including gastrointestinal, pulmonary, neurological, and cardiovascular diseases, with a particular emphasis on malignancies.